Structural Modification of Jackfruit Leaf Protein Concentrate by Enzymatic Hydrolysis and Their Effect on the Emulsifier Properties - Carolina Calderón-Chiu; Montserrat Calderón-Santoyo; Julio César Barros-Castillo; José Alfredo Díaz; Juan Arturo Ragazzo-Sánchez (Colloids and Interfaces, 2022)
Jackfruit leaf protein concentrate (LPC) was hydrolyzed by pepsin (H–Pep) and pancreatin (H–Pan) at different hydrolysis times (30–240 min). The effect of the enzyme type and hydrolysis time of the LPC on the amino acid composition, structure, and thermal properties and its relationship with the formation of O/W emulsions were investigated. The highest release of amino acids (AA) occurred at 240 min for both enzymes. H–Pan showed the greatest content of essential and hydrophobic amino acids. Low β-sheet fractions and high β-turn contents had a greater influence on the emulsifier properties. In H–Pep, the β-sheet fraction increased, while in H–Pan it decreased as a function of hydrolysis time. The temperatures of glass transition and decomposition were highest in H–Pep due to the high content of β-sheets. The stabilized emulsions with H–Pan (180 min of hydrolysis) showed homogeneous distributions and smaller particle sizes. The changes in the secondary structure and AA composition of the protein hydrolysates by the effect of enzyme type and hydrolysis time influenced the emulsifying properties. However, further research is needed to explore the use of H–Pan as an alternative to conventional emulsifiers or ingredients in functional foods.